Serum Fucose Level is a Reliable Biomarker to Astrocytoma: Case-control study-A systematic study and meta-analysis (Open Herald: Periodical of Methodical Research, 2024)
Cancer is one of the main leading diseases causing death. The current study aims to evaluate the concentration of fucose in the blood serum of astrocytoma patients. Also, a systematic study with sequential meta-analysis was performed. Web of Science, PubMed, EBSCO and Scopus, and published reference lists were searched up to end of May 2023. This meta-analysis indicates a statistically significant mean difference in fucose in serum between cancer patients and controls . The current search included 12 of 3611 titles: 562 cancer cases and 401 normal. Meta-analysis concluded that serum fucose can differentiate cancer patients from controls. Significant heterogeneity was found between studies: P < 0.0001 and I2 94.48%. A significant publication bias was observed (Begg, p = 0007; E gger, p = 0. 00092). there was a differences in Forest Plot of TF level between patients and control groups. Also, study estimated pooled effect size